The use of three-dimensional endoscope in transnasal skull base surgery: A single-center experience from China - Xin, Guo; Liu, Yajing; Xiong, Yicheng; Xie, Shenhao; Luo, Hai; Xiao, Liming; Wu, Xiao; Hong, Tao; Tang, Bin (Frontiers in Surgery, 2022)
Objective: The development of skull base surgery in the past decade has been influenced by advances in visualization techniques, recently, due to such improvements, 3-D endoscope have been widely used. Herein, we address the effect of it for transnasal endoscopic skull base surgery. Methods: 63 patients who under endoscopic endonasal surgery (EES) with 3-D endoscope were retrospectively reviewed: including pituitary adenomas, craniopharyngiomas (CP), meningiomas, Rathke`s cleft cysts and chordomas. According to different lesions, transsellar approach (24 cases), transsphenoidal trans-tuberculum approach (14 cases), trans-clival approach (6 cases) and trans-pterygoid approach (19 cases) were selected respectively. Results: Total removal of tumors was achieved in 56 patients (88.9%) and subtotal removal in 7 cases (11.1%). Complications included diabetes insipidus (DI) in 7 patients (11.1%), cerebrospinal fluid (CSF) leakage in 2 patients (3.2%), major vascular injury occurred in 1 patient (1.6%), cranial nerve injury in 9 patients (14.3%), meningitis in 2 patients (3.2%). There was no mortality in the series. All patients had recovered and back to normal daily life, and no tumor recurrence or delayed CSF leakage was detected during the follow-up (2-13 months, mean 7.59 months). Conclusions: Via 3-D EES, it improved depth perception and preserved important neurovascular tissue when removed tumors, which is important for improving the operative prognosis.